Identifikasi Protista sebagai Konten Lembar Kerja Siswa (LKS) untuk Mendukung Pengetahuan Keanekaragaman Hayati di SMA Negeri 42 Jakarta - Rade Ruth Hevila; Fajar Adinugraha; Jendri Mamangkey (Otus Edu Journal Prodi Tadris IPA Biologi UIN Mataram, 2023)
Efforts are necessary to mitigate students' limited understanding of and difficulty in learning about Protista via Student Worksheets (LKS). The creation of such worksheets can be achieved by integrating Protista identification into the surrounding environment. The objective of this research is to identify Protista in the environment of SMA N 42 Jakarta and Universitas Kristen Indonesia as educational resources. Additionally, this study aims to describe the results of the Student Worksheet (LKS), which underwent validation by both validators and students. The research utilized field exploration and development methods. The identification of pond water samples yielded four species: two microalgae and two protozoa. The results of this identification were developed in the LKS uploaded on the ResearchGate link, namely https://bit.ly/LKSprotistaradeetal. The worksheet underwent validation by three reviewers and was deemed feasible with a score above 75%. Additionally, the student feedback was largely positive, with an approval rate exceeding 70%. Thus, the Protista Diversity LKS is expected to be a groundbreaking tool for advancing biodiversity and classification education in 10th-grade classrooms.